Discovering defect-tolerant hybrid perovskites for semiconductor applications - Asebiah, Dominic Cudjoe, author; Neilson, James R., advisor; Sambur, Justin B., committee member; Krapf, Diego, committee member; Rappé, Anthony K., committee member (Colorado State University. Libraries, 2025)
Hybrid organic-inorganic semiconductors with a perovskite crystal structure offer a promising pathway to developing defect-tolerant materials, yet their practical application is often hindered by sensitivity to environmental factors such as moisture, oxygen, and radiation, as well as significant structural disorder. This disorder arises from processing- induced and equilibrium defects and the flexibility of the metal-halide framework with mobile organic species. To better understand these effects, vacancy-ordered double perovskites (A2BX6), which feature isolated [BX6] octahedra connected by A-site cations, provide an ideal platform for studying defects and lattice dynamics in perovskite halide semiconductors. Additionally, tin-based perovskite semiconductors like (CH3NH3)SnI3 are prone to unintentional doping, compromising efficiency and performance. To address this issue, we explore how introducing specific tin vacancies can mitigate these challenges and improve stability and electronic properties. While strategies such as chemical substitution have been shown to suppress the decomposition of hybrid perovskites, the exact chemical and physical mechanisms responsible for these stabilizing effects remain unclear. Chapter two examines the solid solution (CH3NH3)1−xCsxSnBr3, focusing on how thermochemistry and structural distortions influence carrier behavior. In line with first principles and Boltzmann scattering predictions, increasing cesium narrows the optical gap but unexpectedly reduces carrier mobility. This is attributed to increased carrier density and scattering. Synchrotron X-ray scattering reveals cubic symmetry at room temperature, but local distortions suggest anharmonic atomic dynamics. Methylammonium-rich compositions retain linear Sn-Br-Sn bonding, while cesium-rich compositions favor bent environments, increasing defect formation and carrier trapping, explaining anomalous microwave transients. Chapter three reports on (NH3(CH2)7NH3)2Sn3I10, a vacancy-ordered perovskite with three-dimensional connectivity. Its structure resembles a Dion-Jacobson perovskite but with [SnI5] square pyramids bridging the layers. Optical studies reveal a sharp absorption onset, photoluminescence emission, and a large Stokes shift. The conductivity measurements show low carrier mobility and density, suggesting polaron-mediated transport. The equilibrium carrier density of (NH3(CH2)7NH3)2Sn3I10 was found to be remarkably low, despite being a Sn(II)-based material. Fast, fluence-dependent, non-radiative recombination indicates localized defect-like states. The photoluminescence behavior aligns with an asymmetric Sn(II) environment, highlighting defect ordering as a strategy to reduce mobile charge carriers. Chapter four explores the structure-electronic properties of (CH3NH3)1−xCsxPbBr3, highlighting a phase transition from cubic to orthorhombic structures with increasing Cs content and a corresponding shift in the optical bandgap. The TRMC measurements reveal that methylammonium-rich samples exhibit higher carrier densities, mobilities, and dielectric constants. Additionally, photoconductivity exhibits wavelength-dependent behavior, with mobility higher under 600 nm excitation than under 520 nm. Chapter five examines the solid solution between CH3NH3SnBr3 and CH3NH3PbBr3, which retains cubic symmetry at room temperature. The optical bandgap follows a nonmonotonic trend due to bandgap bowing. TRMC measurements reveal wavelength- dependent photoconductivity, with Pb-rich increased mobility under 520 nm. Carrier lifetime increases with Pb content. Chapter six investigates the solid solution between CsSnBr3 and CsPbBr3, revealing a phase transition from cubic to orthorhombic perovskite structures as Pb content increases. The optical bandgap shifts systematically, correlating with unit cell expansion. The TRMC measurements show a nonlinear increase in carrier mobility, while carrier density and conductivity decrease with Pb incorporation. Carrier lifetime is longer in CsSnBr3 than in CsPbBr3. Chapter seven examines the solid solutions of (CH3NH3)2Sn1−xTexI6 and Cs2Sn1−xTexI6, both crystallizing into a cubic vacancy-ordered double perovskite structure. The lattice constants shift systematically with increasing Te incorporation, correlating with optical bandgap trends. The pair distribution function analyses reveal significant local structural distortions in Sn-rich samples. The TRMC measurements indicate a nonlinear decrease in carrier lifetime, conductivity, and mobility with Te incorporation. Carrier mobility remains higher in Cs2Sn1−xTexI6, while carrier density follows a nonmonotonic trend in both systems. Chapter eight chapter explores the structure and electronic properties of (NH3(CH2)7NH3)2Bi2I10 and (NH3(CH2)7NH3)2Sn3I10, emphasizing vacancy ordering and charge transport behavior. The TRMC measurements show higher carrier density and longer lifetimes in (NH3(CH2)7NH3)2Bi2I10, while (NH3(CH2)7NH3)2Sn3I10 exhibits higher mobility due to enhanced non-radiative recombination. These insights highlight vacancy ordering as a key factor in optimizing hybrid optoelectronic materials. Chapter nine presents the synthesis and characterization of SnI2 using an-house PXRD and synchrotron X-ray diffraction data, revealing 99.952(18) wt% phase purity. The optical analysis revealed an indirect bandgap of 1.95(4) eV (636 nm). SnI2 exhibited lower carrier mobility than DFT predictions, with higher carrier density but a shorter lifetime. These findings highlight an efficient synthesis route for high-purity SnI2, reinforcing its significance for fundamental studies and applications. The lattice strain in hybrid perovskites is adjusted through complex interactions driven by organic cation dynamics and chemical substitution. These findings indicate that defect ordering reduces mobile charge carriers at equilibrium by moderating carrier trapping and atomic dynamics. The interplay between high-amplitude atomic motions and low defect formation energies in this highly anharmonic system further highlights the structure- dynamics-property relationship.
Keywords: electrical conductivity; mobility; scattering; electromagnetic radiation; defects; perovskites